Electrically active nanoantenna array enabled by varying the molecular orientation of an interfaced liquid crystal. Issue 87 (6th September 2016) - Hsiao, Yu-Cheng; Su, Chen-Wei; Yang, Zong-Han; Cheypesh, Yevheniia I.; Yang, Jhen-Hong; Reshetnyak, Victor Yu.; Chen, Kuo-Ping; Lee, Wei
Abstract : An electro-optical cell comprising a gold nanoantenna array covered with high-birefringence liquid crystal permits tunability in wavelength of surface plasmonic resonance up to 90 nm. Abstract : A system comprising a gold nanoantenna array covered with a high-birefringence liquid crystal (LC) material is introduced. By applying voltage across the LC bulk, we demonstrate that the refractive-index and polarization changes significantly modify the hybrid plasmonic–photonic resonances in the system. The hybrid structure enables the active control of the spectrum as well as a large shift in resonance wavelength of the metallic nanoantennas by means of an externally applied electric field. Our modeling supports the observed results, by assuming that the nanoantenna array leads to two orthogonal easy axes with a finite anchoring energy. In combination of the nanostructured surface with birefringent LC, tunability up to 90 nm is achieved in the visible wavelengths, opening the door towards nanoscale displays or nano-optical switches.